"www.hate.org" -- The North American White Supremacist Movement: An Analysis of Internet Hate Web Sites - Jones, Allison M. (My University, 1999)
This thesis is a qualitative study of North American white supremacist organisations, and their Internet web sites. Major issues framing the discussion include identity and racism. The thesis takes into consideration Goffman's concepts of 'impression management' and 'presentation of self as they relate to the web site manifestations of 'white power' groups. The purpose of the study is to analyse how a sample of white supremacist groups present themselves and their ideologies in the context of the World Wide Web, and what elements they use as a part of their 'performances', including text, phraseology, and images. Presentation of self intersects with racism in that many modern white supremacists use aspects of the 'new racism', 'coded language' and 'rearticulation' in the attempt to make their fundamentally racist worldview more palatable to the mainstream. Impression management techniques are employed in a complex manner, in either a 'positive' or 'negative' sense. Used positively, methods may be employed to impress the audience with the 'rationality' of the arguments and ideas put forth by the web site creators. Such techniques include the use of euphemistic or pseudo-academic language, allusions to famous figures, non-violence and mainstream issues, and stylistic devices. When used in a negative sense, impression management tactics may be used to strengthen the view of the white supremacist movement as extreme and threatening, to mask what may actually be the weakness and powerlessness of these groups in reality. In this case, explicit and biological language is used, along with vilification, allusions to violence and racist symbolism. Other factors including materials used, size, appearance and interactivity of web sites may affect both the positive and negative performances in complex ways.
Keywords: Sociology; Sociology